Pengembangan Kurikulum Program Literasi Al-Qur’an Jenjang SMA - Nurliah Nurliah (Jurnal Budi Pekerti Agama Islam, 2024)
This article explores the development of a curriculum for the Qur'anic literacy program at the high school level (SMA). The curriculum aims to enhance students' ability to understand and interpret the Qur'an, integrating both traditional religious education and contemporary pedagogical approaches. The study examines the needs of high school students in mastering Qur'anic literacy and how the curriculum can be tailored to meet these needs effectively. The research also addresses the challenges and opportunities in implementing such a program, considering the diversity of student backgrounds and the evolving educational landscape. The findings suggest that a well-structured Qur'anic literacy curriculum can significantly contribute to students' religious and moral development, preparing them to engage with the Qur'an in a meaningful way throughout their lives.